Use of over-the-counter antiallergic products–analysis of sales data in Poland from 2020 to 2023 - Dudziński, Łukasz; Weiner, Marcin; Kubiak, Tomasz; Grochowska, Julia; Gałązkowski, Robert; Czyzewski, Lukasz (Frontiers in Pharmacology, 2025)
ObjectiveThe study aimed to analyse purchasing trends of pharmacological products used in allergy management based on data from in-person pharmacy sales across Poland.Materials and MethodsThe research involved an analysis of the sales of pharmacological agents used to alleviate symptoms of localized and systemic allergic skin reactions. The data were collected from a nationwide sample of 6,500 brick-and-mortar pharmacies over the period from 2020 to 2023. The analysis focused exclusively on over-the-counter (OTC) products.ResultsSales data were classified into three main groups: general antiallergic agents, antipruritic preparations, and products for relief after insect bites or stings. During the observation period, a total of 63.7 million units of allergy-relief products were sold.ConclusionOTC antiallergic medications are widely used, with annual sales reaching millions of units. A clear seasonal trend was observed, with increased purchases during spring and summer months, coinciding with peak allergy seasons. Economic conditions such as inflation appeared to have minimal impact on OTC allergy product sales, likely due to their relatively low cost and high accessibility. Year-to-year purchasing trends remained stable throughout the study period. These findings may support more effective seasonal planning of OTC stock in pharmacies and inform public health initiatives aimed at allergy education and prevention. The stable demand also provides a basis for improving supply chain logistics and forecasting models related to allergy self-management.